نمذجة التصميم التكنولوجي لخط غسيل وتجفيف ألواح الزجاج باستخدام برنامج اﻠ Matlab - سعيد, مي (Latakia University Journal -Engineering Sciences Series, 2014)
يعد الزجاج المزدوج عنصراً مهمّا في الصناعات الحديثة، وهو لوحان من الزجاج المفرد يفصل بينهما عند الحواف طبقة رقيقة من الألمنيوم مملوءة بحبيبات ماصة للرطوبة. ويتم الحصول على لوح الزجاج المزدوج من ألواح مفردة مغسولة ومجففة جيداً، وتُعَدُّ عملية غسيل الألواح وتجفيفها من أهم مراحل تصنيع الزجاج المزدوج، وتتضمن آلة الغسيل والتجفيف للألواح الزجاج ثلاث مراحل. ونظراً للتطور الهائل في مجال التصميم التكنولوجي واستخدام الحاسوب في عملية التصميم كوسيلة تحقق سرعة في التصميم ودقة في الأداء، فقد قام الباحث بإعداد نموذج حاسوبي باستخدام لغة اﻠ Matlabلخط غسيل وتجفيف ألواح الزجاج، ومن خلاله تمّت دراسة العوامل المؤثرة على التصميم التكنولوجي للآلة. The double glass is considered an important element in the modern manufactures, the double glass is tow panes are separated by layer of aluminum at edges full of particles absorbing moisture. we obtain double glass by single panes are washing and drying completely, washing and drying panes is considered the most important stages of making double glass, The washing and drying glass machine consists of three stages. And for great development in the scope of the technology design and using the computer in the design process as a method which is achieved the speed in design and accuracy in the performance, The researcher has prepared programming pattern by using the Matlab program for washing line and drying panes, and by this pattern the researcher has studied the factors which are effective on the machine.